Eficiência, seletividade e análise de custo de herbicidas aplicados em pós-emergência no controle de algodão (Gossypium hirsutum) voluntário, resistente ao glifosato, na cultura da soja (Glycine max) - CLAUDEMIR MARCOS THEODORO (2023)
With the growth in the agricultural sector, crop succession has been a practice increasingly used by rural producers, and in view of this scenario comes the challenges in the management of tigueras from the previous crop, which in turn have the same weed management technology , which consists of resistance to glyphosate, making its use unfeasible to control plants remaining from the previous crop. In chapter 1, the work was carried out with the objective of evaluating tools that add to the management of RR cotton within the soybean crop, for this, four different herbicides lactofen, fomesafen, flumiclorac and imazethapyr were used, in two application moments in the development stages of the culture, V3 and V9, aiming at selectivity and control efficiency. Imazethapyr proved to be more selective for the crop, but it was not efficient in controlling volunteer plants. Lactofen, when applied in V9, caused greater phytotoxic damage and, consequently, a decrease in soybean productivity, but in a single application in V3, it proved to be efficient. The treatments with fomesafen also showed good control efficiency and productivity, while the treatments with flumiclorac were the ones that stood out with the best productivity. In Chapter 2, the aim was to analyze the cost of applying herbicides, where imazethapyr proved to be more economical and selective, but it added the least to productivity, lactofen in a single application in V3 was satisfactory, as well as the treatments with fomesafen. The treatments with flumiclorac were the ones that stood out with the greatest economic gains. It was concluded that for the management of voluntary RR cotton in the soybean crop, flumiclorac proved to be more efficient and with higher productivity at the end of the crop cycle. Imazethapyr showed an increase in soybean productivity, but it was not efficient at any time of application to control voluntary RR cotton. Keywords: Application technology, Economic profitability, Agronomic efficiency.